2009
DOI: 10.1038/npp.2009.66
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant- and Anxiolytic-like Effects of the Phosphodiesterase-4 Inhibitor Rolipram on Behavior Depend on Cyclic AMP Response Element Binding Protein-Mediated Neurogenesis in the Hippocampus

Abstract: Inhibition of phosphodiesterase-4 (PDE4), an enzyme that catalyzes the hydrolysis of cyclic AMP (cAMP), increases phosphorylation of cAMP-response element binding protein (pCREB) and hippocampal neurogenesis, and produces antidepressant-like effects on behavior; however, causal links among these have not been established. In the present study, chronic administration of rolipram produced antidepressant- and anxiolytic-like effects on behavior in mice. It also increased cAMP and pCREB levels in the hippocampus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
139
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 175 publications
(149 citation statements)
references
References 81 publications
8
139
1
1
Order By: Relevance
“…A previous study found that rolipram could increase cAMP accumulation; cAMP accumulation activates cAMP-dependent PKA and subsequently phosphorylates and activates CREB (27). Authors in a different study held the view that rolipram could reduce the distracted platform searches induced by cerebral ischemia (15). In the present study, Fig.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…A previous study found that rolipram could increase cAMP accumulation; cAMP accumulation activates cAMP-dependent PKA and subsequently phosphorylates and activates CREB (27). Authors in a different study held the view that rolipram could reduce the distracted platform searches induced by cerebral ischemia (15). In the present study, Fig.…”
Section: Discussionsupporting
confidence: 63%
“…Therefore, we believe that targeting PDE4 may be an innovative approach to treat cognitive disorders associated with cerebral ischemia. Rolipram, as a prototypical PDE4 inhibitor, is widely used in ischemic stroke studies (15,27). A previous study found that rolipram could increase cAMP accumulation; cAMP accumulation activates cAMP-dependent PKA and subsequently phosphorylates and activates CREB (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this molecular mechanism, the brain-penetrant PDE4 inhibitor rolipram shows memory-enhancing properties in preclinical and clinical models (Fleischhacker et al, 1992;Rutten et al, 2009). In addition, rolipram has beneficial effects in various neuronal systems, for example, increased expression of brainderived neurotrophic factor (Fujimaki et al, 2000) and increased proliferation of neural progenitor cells in the hippocampus (Li et al, 2009), two key effects thought to underlie the antidepressant effects of rolipram. Lastly, the elevation of cAMP in the brain is thought to have beneficial effects in models of tissue injury or neurodegeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of neurogenesis blocks some, but not all, of the effects of antidepressants on behavior (Santarelli et al, 2003;Holick et al, 2008). Likewise, repeated treatment of mice with rolipram also increases hippocampal neurogenesis; inhibition of rolipraminduced neurogenesis reduces antidepressant-like effects on behavior (Li et al, 2009). The relationship among the ability of PDE4 inhibitors to interact with the HARBS and LARBS to alter cAMP signaling, increase neurogenesis, and produce antidepressant-like effects on behavior has not been well characterized.…”
Section: Introductionmentioning
confidence: 99%